Estimating caffeine intake from energy drinks and dietary supplements in the United States. (October 2014) - Bailey, Regan L; Saldanha, Leila G; Gahche, Jaime J; Dwyer, Johanna T
Abstract : No consistent definition exists for energy products in the United States. These products have been marketed and sold as beverages (conventional foods), energy shots (dietary supplements), and in pill or tablet form. Recently, the number of available products has surged, and formulations have changed to include caffeine. To help characterize the use of caffeine‐containing energy products in the United States, three sources of data were analyzed: sales data, data from federal sources, and reports from the Drug Abuse Warning Network. These data indicate that sales of caffeine‐containing energy products and emergency room visits involving their consumption appear to be increasing over time. Data from the National Health and Nutrition Examination Survey (NHANES) 2007–2010 indicate that 2.7% [standard error (SE) 0.2%] of the US population ≥1 year of age used a caffeine‐containing energy product, providing approximately 150–200 mg/day of caffeine per day in addition to caffeine from traditional sources like coffee, tea, and colas. The highest usage of these products was among males between the ages of 19 and 30 years (7.6%, SE 1.0). Although the prevalence of caffeine‐containing energy product use remains low overall in the US population, certain subgroups appear to be using these products in larger amounts. Several challenges remain in determining the level of caffeine exposure from and accurate usage patterns of caffeine‐containing energy products.